2019
DOI: 10.3390/su11102977
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Livelihood Vulnerability of Rural Indigenous Households to Climate Changes in Central Nepal, Himalaya

Abstract: Climate change and related hazards affect the livelihoods of people and their vulnerability to shocks and stresses. Though research on the linkages between a changing climate and vulnerability has been increasing, only a few studies have examined the caste/ethnicity and gender dimensions of livelihood vulnerability. In this study, we attempt to explore how cultural and gender-related aspects influence livelihood vulnerability in indigenous farming mountain communities of the Nepal Himalaya in the context of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Similarly, a gender specific study in Ghana revealed that female headed households, due to their low sociodemographic profile, low social network, and lack of access to water and food, were indicated as vulnerable to the impacts of climate change/variability compared to their counterparts [88]. Moreover, in Central Nepal, limited access to communication and reliable information on climate related hazards and low participation in local based organizations made female head households vulnerable [89].…”
Section: Obstruction Factors Of Communities' Adaptive Capacitymentioning
confidence: 99%
“…Similarly, a gender specific study in Ghana revealed that female headed households, due to their low sociodemographic profile, low social network, and lack of access to water and food, were indicated as vulnerable to the impacts of climate change/variability compared to their counterparts [88]. Moreover, in Central Nepal, limited access to communication and reliable information on climate related hazards and low participation in local based organizations made female head households vulnerable [89].…”
Section: Obstruction Factors Of Communities' Adaptive Capacitymentioning
confidence: 99%
“…Finally, policies aimed at improving livelihood activities in rural communities should focus on economically viable projects. Sujakhu [64] believes that climate change and related hazards seriously affect farmers' livelihoods and their level of vulnerability. Using the Melamchi River Valley, Nepal as a research area, Sujakhu uses the livelihood vulnerability index (LVI) to assess the vulnerability of households in the region in the context of climate change.…”
Section: Construction Of Evaluation Index System For the Welfare Effementioning
confidence: 99%
“…Livelihood strategy includes two aspects: the choices of livelihood strategy and livelihood diversity. Although there is literature that studies rural households' livelihoods in ethnic areas with the sustainable livelihood framework, most studies focus on the construction of evaluation index systems of livelihood capital [19], livelihood vulnerability evaluation [20], and the relationship between livelihood capital and strategy [21,22]. Few empirical studies were conducted to reveal the characteristics of livelihood strategy, especial livelihood diversity of ethnic minority rural households [23].…”
Section: Introductionmentioning
confidence: 99%